Investigating Safety Climate, Safety Performance, and Needlestick and Sharps Injuries in Iranian Hospitals - Fakhradin Ghasemi; Taleb Askaripoor; Hamed Aghaei (Shiraz University of Medical Sciences, 2022)
Background: Needlestick and sharps injuries (NSIs) are a major issue in healthcare settings and should be properly managed. As a type of occupational accident, NSIs are rooted in many causes, including poor safety climate. The current study was conducted to find links among safety climate, safety performance, and NSIs. Methods: The study was cross-sectional and all data were collected in 2020. The sample was composed of 221 nurses. Two dimensions of safety performance and six dimensions of safety climate alongside the experience of NSIs in the last year were investigated using validated questionnaires. The path analysis model was built and tested using Mplus software package. Results: The path analysis model was acceptable in terms of goodness-of-fit metrics. The model supported the mediating role of safety performance on the relationship between safety climate and NSIs. Among safety climate dimensions, safety training had the highest relationship with safety performance dimensions, followed by attitude toward error reporting and cumulative fatigue. Safety participation had a stronger effect on NSIs than safety compliance. Conclusion: As all safety climate dimensions were significantly correlated with safety performance dimensions and NSIs, promoting safety climate can be effective in improving safety performance and preventing NSIs among nurses.